Eficácia de um cenário de simulação clínica para aquisição de competência do enfermeiro para o manejo da hemorragia pós-parto: ensaio clínico randomizado - Coelho, Tatiane da Silva (2023)
This study aimed to evaluate the effectiveness of a clinical simulation scenario for the acquisition of nurses' skills for the management of postpartum hemorrhage (PPH). This is a randomized, blinded clinical trial, carried out at the Maternidade Escola, at the Federal University of Ceará, a tertiary hospital, component of the Zero Maternal Death by Hemorrhage Strategy. The study population consisted of male and female nurses, working in sectors that provide direct maternal care to women in labor and/or in the postpartum period, divided into two parallel groups and randomized by a computer program, in wich allocation was 1:1, based on the randomization. The nurses in the control group participated in an expository class on the management of PPH, in addition to the training commonly provided by the institution for the qualification of the hospital team, and the intervention group which, in addition to participating in the class on the management of PPH, also participated of a clinical simulation scenario for the management of PPH, as an active teaching-learning methodology in the permanent education of health professionals. Data collection took place from October 2022 to March 2023. Data were analyzed using the R 4.2.0 software. The sociodemographic variables and those related to the level of education, sector and length of experience, competence and previous training on PPH were analyzed. For continuous and scalar variables measures of central tendency and dispersion, mean and standard deviation were used respectively. Categorical variables were analyzed according to relative and absolute frequency. The Wilcoxon test was used to compare the medians of two independent samples. Distributions of categorical variables were compared using the Chi-square or Fisher's exact test. The final sample consisted of 37 nurses, mostly female (78.4%) and mean age of 40 years, with (70.2%) specialists in different areas. About 91% of the nurses reported having experienced assistance to a puerperal woman with PPH, however, approximately 30% of them stated that they did not feel prepared for the management of PPH, due to fear/insecurity or lack of knowledge. In the post-intervention evaluation, the average of correct answers in the post-test in the intervention group increased by 4x and in the control group by 3x. The educational intervention, using the simulation scenario, proved to be effective for the teaching-learning process of nurses in the management of postpartum hemorrhage. The authors recommend the use of clinical simulation as a teaching strategy for the permanent education of nurses, with a view to improving cognitive performance, skills and attitudes, in addition to improving clinical judgment, autonomy, confidence and satisfaction of nurses in the management of postpartum hemorrhage.